Analisis Jaringan Komunikasi Community Development Program Kampusng Tangguh Plus Peduli Anak Kelurahan Wonokusumo Kota Surabaya - Dewantari, Lukyta (The Commercium, 2022)
The focus of this research is the role of communication networks in community development, especially in the issue of child protection which is a problem in developing countries. This study presents an analysis of how the efforts of the child care village task force actor in obtaining the information needed through a communication network approach. Communication networks are used to identify the role of community development because communication networks can describe actor relationships that cause individuals to be encouraged to interact. The research objectives are (1) to analyze the structure of the communication network and identify the roles of actors. (2) explain how the communication network in community development is to form a social program for a tough village to care for children. This study uses a quantitative approach by distributing questionnaires to 37 communication actors using a small group sample. The results showed that (1) the network structure is centralized with a low level of connectedness between actors, the role of actors is dominated by actors Kustana, Ali, Ernawati, Sujali, Nancy, and Didid. (2) The communication actor is dominated by individuals who have homophilic characteristics, the formation of a tough village program is based on two mechanisms, namely the selection process and social influence. Keywords: Communication Network, Community Development, Child Protection